EVALUASI PENGGUNAAN METODE VALUE ENGINEERING PADA PEKERJAAN KONSTRUKSI JEMBATAN SEI IDAN KABUPATEN KUTAI BARAT - Donal Yusuf Hutauruk; Habir; Syahrul (Media Bina Ilmiah, 2025)
This study evaluated the application of the Value Engineering method in the construction of the Sei Idan Bridge in Kutai Barat Regency to identify cost-saving opportunities without reducing structural function and quality. The analysis was carried out through six stages, focusing on four dominant work items identified using Pareto analysis: Grade 345 steel, U-Type DS-1 drainage, BjTS 420B reinforcement, and fc’30 concrete. Technical alternatives were developed through brainstorming and assessed in terms of technical performance, cost, and implementation risks. Feasibility was evaluated using the Analytical Hierarchy Process method based on six criteria. The results showed that the Q345B alternative achieved a cost efficiency of 58.35% and was deemed feasible with quality testing requirements. Other alternatives, such as Precast HDPE, HS Rebar fy 500 MPa, and Precast Concrete, also demonstrated high efficiency. The Value Engineering method proved effective in optimizing bridge construction costs through a systematic and function-based approach.